Practices of Community and Place Narratives for IT.A.CÀ Salento 2021. The Case #39 of A.Lib.I. Teatro - Miggiano, Patrizia Domenica; Longo, Mariano (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
The paper intends to problematize the relationship between community narrative practices and territorial identities, investigating the capacity of the former to influence the social perception of places and their development. Translating this relationship of influence into a valorisation practice means understanding that the ability to know how to read a story in places makes a difference among stakeholders today, as it determines a culturally sustainable development plan, through the use of practices that steer the direction of cultural and economic growth of a territory and that at the same time determine the possibility for local communities to re-appropriate a common narrative-cultural matrix. Within the framework of these considerations, there are some particular projects conceived and realised within the framework of the I.ta.cà. Responsible Tourism Festival, which since 2008 has intercepted and made its own the desire to propose sustainable travel models attentive to the involvement of communities and the sustainable development of territories. This is particularly the case of the stage of I.ta.cà. Salento 2021, which saw the realisation of a rich and complex dramatised itinerary among the Salento localities of Marina Serra, Tiggiano, Lucugnano, Tricase, Tricase Porto, Biotopo delle Vallonee, Porto Museo, and Castiglione d’Otranto del Serra Mito. The event also included and offered to the public a performative restitution by the cultural association A.Lib.I. (Artisti Liberi Indipendenti), which has been working in the Salento area since 2013, mostly through theatrical performances and dramatisations aimed at the valorisation and narration of local material and immaterial sediments. In particular, by means of a semi-structured interview with director Gustavo D’Aversa, an attempt was made to investigate the social implications of their work and of the community performance entitled #39 by Walter Prete, which recounts a complex chapter of local history, the story of the local refugee camp (Displaced Persons Camp), active in Tricase during the Second World War, from 1943 to 1948. The performance was entrusted to local people, volunteer and non-professional actors, who told contemporary fellow countrymen about the difficulties that arose in their town with the arrival of the Jewish refugees. A tale from the people of Tricasini for the people of Tricasini, which proposes an experimental way of telling the story of the territory and for this reason stands as an interesting case study for reflecting on the opportunity, through narrative practices, to intercept and satisfy the needs and desires of a community and to attempt to compose a mapping of cultural instances to which to offer answers.